Peningkatan Manajemen Mutu Pos PAUD Melati 10 dan Kenanga 12 Menuju Persiapan Akreditasi PAUD - Ratu Fenny Muldiani; Kunlestiowati Hadiningrum; Siti Syamsiah Purwaningsih; Nani Yuningsih; Anie Lusiani (LPPM UNINUS, 2020)
POS PAUD is one of the non-formal educational institutions that plays an important role in children's education. All learning activities in PAUD and the supporting facilities must meet the standards according to the provisions of PAUD Education. To find out the achievement of these standards accreditation activities are needed, because one of the efforts to maintain the quality and improvement of an educational institution is through accreditation activities. POS PAUD Melati 10 and Kenanga 12 are located in Kelurahan Pasir Kaliki Kecamatan Cimahi Utara are PAUD institutions that have not been accredited. In order for POS PAUD to be accredited properly, it must meet the accreditation eligibility criteria based on the National Education Standards which include eight standards.. The methods used in the preparation of the two POS PAUD accreditations are literature study, interviews, field surveys, discussions, technical guidance for preparation of accreditation standard documents in the form of workshops for school principals, teachers and operators. Through this accreditation preparation assistance activity, it has succeeded in bringing POS PAUD Melati 10 to meet the accredited criteria and POS Kenanga 12 PAUD with additional time being ready for accreditation.